Instabilities in the Bottom Boundary Layer Reduce Boundary Layer Arrest and Stir Boundary Layer Water Into the Stratified Interior. Issue 4 (21st April 2022) - Pringle, James M.
Abstract: An along‐isobath current in stratified waters leads to a bottom boundary layer. In models with no alongshore variation, cross‐isobath density transport in this bottom boundary layer reduce the velocity in the bottom boundary layer via thermal wind, and thus the bottom friction experienced by the current above the boundary layer—this is bottom‐boundary‐layer arrest. If, however, alongshore variation of the flow is allowed, the bottom boundary layer is baroclinically unstable. We show with high resolution numerical models that these instabilities reduce this arrest and allow bottom friction to decelerate the flow above the bottom boundary layer when the flow is in the Kelvin wave direction (so that the bottom Ekman transport is downwelling). Both the arrest of the bottom boundary layer and the release from this arrest are asymmetric; the friction experienced by flows in the direction of Kelvin‐wave propagation (downwave) is much greater than flows in the opposite direction. The strength of the near bottom currents, and thus the magnitude of bottom friction, is found to be governed by the destruction of potential vorticity near the bottom balanced by the offshore along‐isopycnal transport of this anomalous potential vorticity. A simple model of this process is created and used to quantify the magnitude of this effect and the resulting reduction of arrest of the bottom boundary layer. Plain Language Summary: It has long been thought that alongshore flows over the shelf and slope will, over time, change the cross‐shelf distribution of salt and temperature near the bottom such that the flow at the bottom is small. This reduction in near‐bottom flow reduces the friction between the alongshore flows and the bottom, in theory allowing the water to flow forever along the coast. This work shows, instead, that this cessation of flow near the bottom does not happen. Building on existing understanding of how the near bottom flow can break up into eddies, this work quantifies how much friction the alongshore flow feels, and finds it is greater than had been understood when the flow has the coast on its right in the Northern Hemisphere, and on its left in the southern Hemisphere. The eddies created near the bottom take fluid from near the bottom and inject it into the adjacent stratified ocean. This links the near bottom waters, with their distinct chemistry, to the deep waters of the ocean. Key Points: Instabilities in the bottom boundary layer prevent the arrest of the bottom boundary layer for along‐isobath flows in the Kelvin wave direction, enhancing bottom drag Instabilities in the bottom boundary layer transport water from the bottom boundary layer into the stratified interior along isopycnals for flows in the Kelvin wave direction These processes can be understood as the balance between potential vorticity destruction near the bottom and eddy‐driven potential vorticity fluxes from the stratified interior to the bottom